Assessing academics' third mission engagement by individual and organisational predictors - Verena Karlsdottir; Magnus Thor Torfason; Ingi Rúnar Eðvarðsson; Thamar Melanie Heijstra (Administrative Sciences, 2023)
In recent years, the coming of the entrepreneurial university has brought about a third role in academia, which involves greater visible exchange of academics with society and industry. In this paper, the authors investigate to what extent individual and organisational factors influence the propensity of academics to engage in different types of Third Mission (TM) activities. This study is based on a large-scale survey of academics in Iceland regarding engagement in socio-economic activities. The results indicate that "soft" activities such as community activities and external teaching and training can be better predicted by individual factors, while hard activities such as applied contract research and commercialisation can be better predicted by organisational factors. Overall, academics are most likely to participate in community-related activities. Hereby, academics from the STEM and health disciplines, with work experience outside of academia and who are open to new experiences are more likely to be engaged in applied contract research and commercialisation. Academics belonging to disciplines other than STEM and health sciences and those that on an average publish more peer-reviewed articles are more likely to disseminate their knowledge to a wider audience outside of academia through public science communication. Gender, rank, and teaching do not affect TM participation, but openness, performance, or discipline do.
Keywords: 350; commercialisation; contract research; entrepreneurial university; personality traits; science communication; third mission